2021
DOI: 10.29045/14784726.2021.3.5.4.40
|View full text |Cite
|
Sign up to set email alerts
|

Hangings attended by emergency medical services: a scoping review

Abstract: <sec id="s1"> Background: In the United Kingdom (UK) there were 6507 deaths by suicide in 2018, with hanging being the most common method. Hanging will normally result in emergency medical services (EMS) being called and may result in resuscitation being attempted. Trauma audits conducted by North East Ambulance Service NHS Foundation Trust have identified an increased trend in hanging cases, which were also reported in national data. The aim of this scoping review was to explore the literature around E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The population described was largely young males, which reflects national trends ( ONS, 2020 ) and data from a neighbouring ambulance service ( Hayden et al, 2021 ). Paediatric hangings were thankfully rare and reflected previously reported patterns ( Shaw et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The population described was largely young males, which reflects national trends ( ONS, 2020 ) and data from a neighbouring ambulance service ( Hayden et al, 2021 ). Paediatric hangings were thankfully rare and reflected previously reported patterns ( Shaw et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
“…The following data, including 58 individual fields, were selected by the authors as being relevant to hangings based on a previous scoping review ( Shaw et al, 2021 ). Data were manually extracted from the ePCRs by the authors and sorted into the following domains:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A suicide attempt is an emergency, and as such requires immediate decisions to be taken to safeguard the threatened life. In addition, actions need to be taken to reduce the risks to the safety of the victim and the professionals involved [ 21 ]. Emergency professionals are used to assisting patients who are struggling to live, and this issue breaks the mental model of the responders and can have a profound impact on them if the suicide is completed and, above all, witnessed [ 22 ].The role of these professionals becomes crucial in treatment as well as prevention to provide a good quality of care from the first second of attendance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that compared to the Northeastern region, firearm suicides are more common in states in the Western, Midwestern, and Southern regions where firearm ownership rates are higher ( 9 , 11 ). While research on hanging/suffocation in other counties has been extensive ( 12 , 13 ), there is a paucity of research on hanging/suffocation in the U.S. Thus, we did not posit any hypothesis regarding its clinical correlates; however, based on the increasing use of hanging/suffocation among younger age groups, we hypothesized that those age under 45 would be more likely to have used this method.…”
Section: Introductionmentioning
confidence: 99%